The Spanish Labour Market at the Crossroads: COVID-19 Meets the Megatrends - Juan J. Dolado; Florentino Felgueroso; Juan F. Jimeno (Institute of Labor Economics (IZA), 2020)
This paper reviews the experience so far of the Spanish labour market during the Covid-19 crisis in the light of current institutions, past performance during recessions, and the policy measures adopted during the pandemic. Emphasis is placed on the role of worldwide trends in labour markets (automation and AI) in shaping a potential recovery from this (hopefully) transitory shock through a big reallocation process of employment and economic activity.
Keywords: J64; J68; 330; epidemic; COVID-19; dual labour markets; flows; recessions